Shift from the instrumental to the existential interpretation of baptism in the Catholic tradition - Sannikov, Sergey (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2019)
The article examines the history and doctrinal comprehension of the phenomenon of water baptism in the Catholic tradition. It shows the origins of the traditional understanding the baptism as a sacrament, where the grace is transmitted; it demonstrates the history of the formation the “ex opere operato” formula. Author underlines the contradictory position, role and place of faith for a person, who accepts grace. The text highlights the main discussions on the understanding of this sacrament. The author emphasizes the importance of new trends in the works of contemporary Catholic theologians, who transfer the emphasis in the understanding of baptism from its instrumental to the existential action. Such shift beyond instrumental understanding allows moving attention from the legal aspects of the legality and validity of the sacrament to the periphery and removing many practical questions arising from the primitive perception the baptism as a magical act. The article also analyzes the internal contradiction of baptism as a sacrament of faith in the situation of infant baptism, who are baptized “by the faith of others” (the godparents or the Church as a whole)